2014
DOI: 10.2113/jeeg19.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 2-D ERT in Investigation of Abnormal Seepage: A Case Study at the Hsin-Shan Earth Dam in Taiwan

Abstract: There is a great demand for effective non-destructive methods to examine the interior of reservoir structures, such as dams. The present study was aimed at assessing the performance of electrical resistivity tomography (ERT), a popular non-destructive testing method, to investigate leakage at an earthen dam. Several abnormal leaks appeared on the downstream face after the dam was reconstructed to raise the maximum reservoir water level. Three 2-D ERT surveys were deployed on the left abutment, dam crest, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…As the 2D resistivity profile had a 3D effect, the authors established the 3D forward modeling of the Hsin-Shan Earth Dam, and compared the differences between the 2D resistivity profile after inverse computing and the Hsin-Shan Earth Dam model. The results showed that the 2D resistivity profile was indeed affected by the 3D effect and had an irregular resistivity distribution [10]. Both the results of this study and Lin et al (2013) found that the 2D ERT had a 3D effect.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…As the 2D resistivity profile had a 3D effect, the authors established the 3D forward modeling of the Hsin-Shan Earth Dam, and compared the differences between the 2D resistivity profile after inverse computing and the Hsin-Shan Earth Dam model. The results showed that the 2D resistivity profile was indeed affected by the 3D effect and had an irregular resistivity distribution [10]. Both the results of this study and Lin et al (2013) found that the 2D ERT had a 3D effect.…”
Section: Discussionmentioning
confidence: 52%
“…The results showed that the 2D resistivity profile was indeed affected by the 3D effect and had an irregular resistivity distribution [10]. Both the results of this study and Lin et al (2013) found that the 2D ERT had a 3D effect. However, the results of this study explored the effects of various influencing factors on the 3D effect and boundary effect in depth, and should be avoided as much as possible in future detection.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…ERT has been found as a good nondestructive technique, which gave the possibility of detecting internal erosion processes and to detect anomalous seepage (Sjödahl et al 2006(Sjödahl et al , 2010Cho and Yeom 2007;Lin et al 2014), at an early stage before the stability of the dam was compromised. In association with ERT, geophysical techniques such as electromagnetic scanning and self-potential have been suggested as non-invasive methods for examining internal embankments conditions (Sentenac et al 2013(Sentenac et al , 2017Jones et al 2014;Utili et al 2014;Ikard et al 2014;Bolève et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This presentation focuses on the discussion of ERT. The electrical resistivity tomography (ERT) is one of the most widely used geophysical methods in geological, hydrogeological, and geo-environmental investigationsp [3,4] . Although 3D ERT is now available, 2D ERT remains to be state-of-the-practice due to its simplicity in field works and less requirement in space and equipment.Since the purpose of the geophysical monitoring is to scan potential anomalies in any location of the dam, the whole extent of the dam in the longitudinal direction are covered by 2D ERT survey lines both on the core and downstream shell.…”
Section: Introductionmentioning
confidence: 99%